Effectiveness Of Project Based Learning Model (Pjbl) Based On Higher Order Thinking Skill (Hots) On Problem Solving Ability Of Grade V Students In UPT SPF SD - Santi, Santi; Irviana, Ira; Mursidin, Muthmainnah (ALENA : Journal of Elementary Education, 2025)
This study aims to determine the application of the Project Based Learning (PjBL) learning model based on Higher Order Thinking Skill (HOTS) to problem solving skills in IPAS learning for grade V students at UPT SPF SD Negeri KIP Maccini and the effectiveness of the Project Based Learning (PjBL) learning model based on Higher Order Thinking Skill (HOTS) on problem solving skills in IPAS learning for grade V students at UPT SPF SD Negeri KIP Maccini Makassar City. This type of research is experimental research with a one group pretest-posttest design with a sample size of 22 students consisting of 15 male students and 7 female students using observation sheet instruments, tests, questionnaires and documentation. In this study using descriptive statistical analysis and inferential analysis with the help of SPSS version 29. The results of this study indicate that after using the Project Based Learning (PjBL) learning model based on Higher Order Thinking Skill (HOTS), the mean posttest test is 76.77 and the mean posttest questionnaire is 45.22. Based on the hypothesis test that has been carried out, it can be concluded that the Project Based Learning (PjBL) learning model based on Higher Order Thinking Skill (HOTS) has an effect on students' problem solving ability after a value of 0.000 <0.05 is obtained so that H0 is rejected and H1 is accepted, which means that there is a significant effect of using the Project Based Learning (PjBL) learning model based on Higher Order Thinking Skill (HOTS) in IPAS learning on the problem solving ability of grade V students.